Pelatihan dan pembentukan klub majalah dinding sebagai upaya peningkatan literasi kesehatan pada siswa SMPN 39 Samarinda - Nur Rohmah; Silfa Ayu Safika; Muh Azmi Muhidin (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
The SMP Negeri 39 Samarinda students' activities have changed, if not stopped altogether, as a result of the teacher and student activities switching from online learning to face-to-face learning. The same goes for wall magazines, which are meant to foster students' creativity and reading. Because there is no organization or club and students are not aware of how to manage wall magazines, the state-of-the-wall magazines at SMPN 39 Samarinda were inadequate. The formation of a wall magazine club and instruction in creating health-based wall magazines are two activities done to increase students' health literacy. At SMPN 39 Samarinda, there is student involvement and competence in creating wall magazines, as well as the development of a management structure and a detailed work plan for the wall magazine club.